2016
DOI: 10.4103/2279-042x.179582
|View full text |Cite
|
Sign up to set email alerts
|

Attachment to stress ulcer prophylaxis guideline in the neurology wards of two teaching and non-teaching hospitals: A retrospective survey in Iran

Abstract: Objective:In this study, we aimed to evaluate the attachment to stress ulcer prophylaxis (SUP) guideline in the neurology wards of two teaching and nonteaching hospitals.Methods:A total of 243 patients were retrospectively reviewed in the neurology wards of two teaching and nonteaching hospitals. To assess the appropriate administration of SUP, an internal guideline was prepared using the American Society of Health-System Pharmacists (ASHP) protocol.Findings:SUP prescriptions were noncompliant with ASHP guidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 10 publications
2
14
3
Order By: Relevance
“…Our claim was supported by many studies which revealed SUP usage in academic centers was more compliant with the guidelines than nonacademic hospitals. 18,26,30…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our claim was supported by many studies which revealed SUP usage in academic centers was more compliant with the guidelines than nonacademic hospitals. 18,26,30…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with other studies. 19,22,29 According to Foroughinia and Madhooshi, 18 coagulopathy was the only absolute indication for SUP. Mechanical ventilation and burn were not found as an indication for SUP in the this study, while some other studies reported so far found mechanical ventilation as a common indication for SUP use.…”
Section: Discussionmentioning
confidence: 99%
“…According to ASHP guideline and recent performed studies, patients who had 1 absolute indications or at least 2 of the relative indications were eligible for SUP administration in non-ICU setting ( Table 1 ). 8 , 12 , 16 , 17 …”
Section: Methodsmentioning
confidence: 99%
“…These results were consistent with earlier studies. [1622] We relatively identified a large number of patients continuing SUP medication with lack of risk factors in emergency department than the patients admitted to the internal medicine department. These findings are similar to those obtained by Mohamad et al .,[23] who observed that approximately 57.8% of patients had no risk factors and received unjustified prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Iran reported that almost 85% of the SUP agents administered to hospitalized patients were inappropriately prescribed. [16] Another prospective study reported that ASTs had been prescribed for SUP to 44.4% of patients without an appropriate indication. [17] Herzig et al .…”
Section: Introductionmentioning
confidence: 99%